PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) UNTUK MENYELEKSI PENERIMA BANTUAN LANGSUNG TUNAI DANA DESA (BLT DD) - Oviletta Aurellia; Untoro Apsiswanto (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
With many government programs to improve the social status of the community, one of which is the Village Fund Direct Assistance (BLTDD) program in Pujo Basuki Village, Central Lampung, with the hope that the community's economy can be helped by this program. Selecting the right beneficiary to receive such assistance must be done in a precise and accurate manner. From these issues, it is necessary to have a method to support decision making in order to determine the residents of this assistance program appropriately with the SAW (Simple Additive Weighting) method in the process of making a decision..